(untitled) (ENTHYMEMA, 2023)
Many of Levi’s speculative stories narrate dystopian scenarios in which individuals express anxiety about the creeping power of technology which is reifying and automating their posthuman bodies, affecting their physical and psychological freedoms. This article develops previous scholarship with a specific focus on the gendered dimension of Levi’s writing. I show how he critiques the problematic ways in which technologisation impacts specifically on women’s bodies. With a view to tracing the contemporary echoes of Levi’s work, I place his stories in dialogue with Nicoletta Vallorani’s recent, more explicitly feminist novels. I argue that Vallorani’s writing echoes and develops many of Levi’s concerns about how technology can be employed to constrain our bodies and consciousness, and the explicitly gendered dimensions of this oppression. A critical reading of these texts alongside one another reveals striking resonances and confirms how Levi’s intuitions regarding the importance of critiquing unfettered technologised embodiment remain urgently relevant today.